2008
DOI: 10.1183/09031936.00130807
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and asthma in the E3N study

Abstract: The aim of the present study was to determine dietary patterns and investigate their association with asthma incidence, current asthma and frequent asthma exacerbations.Dietary habits and asthma data were collected from the large E3N study (of French females, mostly teachers). Of the 54,672 females followed-up in 2003, 2,634 reported ever-adulthood asthma, 1,063 reported current asthma, 206 reported frequent asthma attacks (one or more a week), and 628 reported asthma onset between 1993 and 2003. Using princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 29 publications
2
94
1
Order By: Relevance
“…A study of Chinese Singaporeans found that a diet rich in meats, Na and refined carbohydrates was positively associated with habitual cough and phlegm (7) , while a study of Japanese female students found that a butter and rapeseed oil dietary pattern, and a fast-food, soft drink and juice dietary pattern were both positively associated with wheeze (8) . In France, a study of female teachers found that a pastry, processed meat and dessert pattern was positively associated with reporting frequent asthma attacks, and a nut and wine pattern was negatively associated (9) . One problem with the PCA approach is that it does not lend itself well to the synthesis of evidence from different studies.…”
mentioning
confidence: 99%
“…A study of Chinese Singaporeans found that a diet rich in meats, Na and refined carbohydrates was positively associated with habitual cough and phlegm (7) , while a study of Japanese female students found that a butter and rapeseed oil dietary pattern, and a fast-food, soft drink and juice dietary pattern were both positively associated with wheeze (8) . In France, a study of female teachers found that a pastry, processed meat and dessert pattern was positively associated with reporting frequent asthma attacks, and a nut and wine pattern was negatively associated (9) . One problem with the PCA approach is that it does not lend itself well to the synthesis of evidence from different studies.…”
mentioning
confidence: 99%
“…Briefly, food items were grouped a priori into 56 separate food groups and, as previously described [9], three dietary patterns were obtained from these food groups: a ''prudent'' pattern (high intake of fruit and vegetables), a ''Western'' pattern (high intake of pizza/salty pies, desserts, cured meats and pasta) and a ''nuts and wine'' pattern (high intake of nuts and seeds, salty biscuits, olives, wine and fortified wine) [9]. Each dietary pattern score was categorised into tertiles (tertile 1: the lowest score; tertile 3: the highest score).…”
Section: Farming Lifestylementioning
confidence: 99%
“…The overall prevalence of childhood asthma was 1.6% and of adult-onset asthma, 3.2%. Frequent asthma attacks were defined by a report of one or more attack per week in the last 12 months [9]. As the study was carried out by postal questionnaire, there was no lung function test.…”
Section: Asthma Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Therefore, if the diet is supplemented with these ingredients since childhood asthma can be prevented. 9,10,12 Others have inconclusive results as far as the role of dietary pattern in asthma prevention and treatment is concerned. 14,16 Although there have been numerous studies more population based study are required to established the association asthma, allergy and diet.…”
Section: Introductionmentioning
confidence: 99%